Bilateral Finger Morton Neuroma after Primary Fingertip Amputation. Issue 1 (27th January 2022) - Mogl, Adrian Georg; Gualdi, Alessandro; Kamolz, Lars-Peter; Sarocchi, Francesca; Cambiaso-Daniel, Janos
Abstract : Summary: Morton's neuroma (MN) is a painful, proliferative fibrosis of perineural tissue caused by pressure or recurrent irritation that was previously thought to affect only the common interdigital nerve of the foot. We present a case of a bilateral MN of both the ulnar and radial proper digital nerves of the fifth finger in a 30-year-old patient, following multiple surgeries on the aforementioned finger. The patient was referred to our center by a peripheral hospital after traumatic fingertip amputation distal the DIP joint, where the fingertip was initially simply sutured. Because of progressive neuropathic pain, he underwent two revision surgeries, in which the distal phalanx was removed, two neuromas were excised, and the nerve stumps were shortened, but both were unsuccessful. A final, more extensive revision surgery was then carried out, in which two club-like enlargements were excised and the nerve stumps coadapted to form a loop. Histopathological examination of the excised specimen revealed perineural fibrosis in the context of a Morton's neuroma. This is, to our knowledge, the first documented case of a bilateral MN of the hand, which may have resulted from an inadequate primary finger and nerve shortening, resulting in high pressure from the surrounding soft tissue. Finally, this report emphasizes the significance of optimal treatment for finger amputation injuries, as well as the fact that for neuromas, simple nerve resection should be avoided whenever possible, because of the high recurrence rates.